Y.H. Brenner's World War I stories - Guy, Tsippora (School of Languages and Literatures, 2026)
The subject of this thesis is those short stories of Y.H. Brenner which have as their background the First World War - in particular, the invasion of Northern Israel by the British, and the expulsion of the Jews from Tel Aviv - Jaffo and Petah Tikvah by the Turks. With the exception of "Ha-motsah11 , there hardly exists a critical analysis and commentary on these stories, and thus the major purpose of this thesis is to illustrate the literary craft of Brenner and to give a commentary on each of these stories. The subject matter of each story is pared down and limited to one cogent issue. The external world crisis is used by Brenner to expose the bitter truth about the state of the Jewish settlement in Israel. In some of the stories he examines the influence of this crisis on the Jewish settlers, not as individuals, but as the potential realizers of the Zionist dream. The stories can be divided into two groups. In the first group are the stories “Ha-Motsah” , “Ha-Geulah ve 'ha-temurah” , and “Avlah” , while the second group consists of the sketches “Gazlanim” , “Asonot” , “Tsava'ah” , and “Mazal” (collectively called by Brenner “Ze-er Sham"). In the first group of stories, the narrator attempts to create a model through which he can relate to the Zionist dream. On a deeper level, these stories deal with the nature of Jewish existence - national exile and redemption. The stories in this group are outstanding in their irony and pessimism. Their characters fail not only because of personality defects but also because the author confronts them with the humanistic and national ideals that they bear with them. In the second group of stories, Brenner does not deal with the realization of the Zionist dream, but mainly with human and moral questions. The characters are people who have, because of historical circumstances outside of their control, become enmeshed in tragic situations, and the crisis of the war exposes their hidden limitations or depths. The central characters are marginal figures. They are not people of status nor do they have conscious national aspirations. The war catapults them into conflicts that reveal to them the mystery and complexity of life, and the author's attitude to them is one of compassion and sympathy. All the stories provide evidence of Brenner's maturity as a writer of authentic and realistic stories which, at the same time, also have a complete artistic integrity. In this thesis it becomes clear that Brenner's primary commitment is to the artistry of his work, and evidence for this is provided by the free use he makes of auto-biographical and historical material. For artistic reasons, he feels free to include, emphasize, embroider, omit or downplay this material. Brenner sees the present in a broad historical perspective, and this is expressed in the interweaving of biblical myths and literary sources, even though, for various reasons that are elaborated on in this thesis, he chooses to blur their presence. Characters and motifs from the past carry on a type of dialogue with the present, and this is mainly done in order to confront the present and to show it in an ironical light.